NEUROLOGICAL COMPLICATIONS IN PREMATURE NEWBORNS WITH HEMOSTASIS DISORDERS (Herald of the National Children's Medical Center, 2022)
In order to study changes in hemostasis, 77 newborns with hypoxic-ischemic lesions of the central nervous systemwere examined. Depending on the neurological status and neurosonogram data, all children were divided into three groups:healthy children (group I); premature newborns with moderate CNS damage without hemorrhagic manifestations (group II);premature newborns with severe CNS damage, with hemorrhagic manifestations (group III). It is shown that the violation ofhemostasis should be regarded as universal pathogenetic factors of the development of ischemic-hemorrhagic disordersthat determine the development of cerebral deHciency of varying severity.
Keywords: premature newborns; hemostasis system